Análisis a los estados financieros de empresas camaroneras en la provincia de El Oro, Ecuador - Muñoz Briones, Juan Carlos (2018)
This research is focused on the analysis of the economic situation according to results of the financial statements of the shrimp sector in the Huaquillas, Arenillas and Santa Rosa cantons of the province of El Oro, in recent years, in order to determine its financial indicators as are liquidity, indebtedness and profitability, as well as evaluating their working capital; the methodology developed in this research is descriptive, using a non-experimental design of longitudinal type, whose relevant results within the research process is that the shrimp sector lives one of its greatest boom years, due to its technological advances , the knowledge domain, the increase in its production and the permanence of its highest quality, this brings with it that there is a greater demand in the national and international market, to determine the variables Pearson correlation was used with the purpose of to determine the relationship between variables analyzed, such as utility, debt and investment, in addition to the analysis of the accounts of assets, liabilities, equity, income, and costs / expenses, which allow the real situation of companies to be determined, understanding of their results and strengthening sustainability by making appropriate decisions in relation to results reasonable.